Doing Justice, Becoming the Just Man: Eckhart on Our Deiformation. Issue 2 (2nd July 2016) - Murphy, Gregory
Abstract : In his teaching and preaching Meister Eckhart, following on and developing the thought of his confrere Thomas Aquinas, was primarily concerned to guide his hearers into forming and living out an ever-closer union with God as they become more deeply disciples of Christ. In this, he was articulating in a new way what the Eastern Church Fathers called Deification, the Christian disciple becoming holy, or like to God. This concept was common in the Western tradition, though more usually expressed there as the disciples conforming themselves to Christ. In both, the path of discipleship is presented as a movement from a position of estrangement to union. Eckhart is sometimes accused of conflating the distinction between Creator and creatures, but this is to misread him. I here draw on recent readings of Eckhart to suggest that in his theology his language of the relationship while always analogical moves from an almost equivocal analogy of attribution—in which truth, justice, goodness, even existence—are lent to the creature by God; to a use of univocal language to express unicity or union in which the creature allows God to negate any distinction between itself and the Creator—the condition of union—in which the creature reflects to some degree the divine perfections, becoming good, just, loving—in a word, holy. I suggest that this shift in language is meant to be descriptive of the process of discipleship: essentially, the partially estranged creature accepting the Creator's call to union.